The age‐related increase in low‐grade systemic inflammation (Inflammaging) is not driven by cytomegalovirus infection - Bartlett, David B.; Firth, Charlotte M.; Phillips, Anna C.; Moss, Paul; Baylis, Daniel; Syddall, Holly; Sayer, Avan A.; Cooper, Cyrus; Lord, Janet M. (Aging cell, 2012)
Summary Aging is accompanied by the development of low‐grade systemic inflammation, termed ‘inflammaging’, characterized by raised serum C‐reactive protein (CRP) and pro‐inflammatory cytokines. Importantly, inflammaging is implicated in the pathogenesis of several of the major age‐related diseases including cardiovascular disease, type 2 diabetes, and dementia and is associated with increased mortality. The incidence of infection with the persistent herpes virus cytomegalovirus (CMV) also increases with age. Cross‐sectional studies have proposed CMV infection as a significant driver of inflammaging, but a definitive case for CMV as a causative agent in inflammaging has not yet been made. We studied longitudinally 249 subjects (153 men, 96 women) who participated in the Hertfordshire Ageing Study at baseline (1993/5, mean age 67·5 years) and at 10 year follow‐up. At both times, anthropometric measurements were made and subjects provided blood samples for analysis of inflammatory status and CMV seropositivity. In the cohort as a whole, serum CRP (P < 0·02) and pro‐inflammatory cytokines TNFα (P < 0·001) and IL‐6 (P < 0·001) were increased between baseline and follow‐up sampling whereas levels of the anti‐inflammatory cytokine IL‐10 were decreased (P < 0·001). These changes to cytokine status over time occurred equally in the 60% of subjects who were seropositive for CMV at baseline and follow‐up, the 8% who were CMV negative at baseline but who became CMV positive by the 10 year follow‐up, and also in the 32% who were CMV seronegative throughout. We conclude that CMV infection is not a primary causative factor in the age‐related increase in systemic inflammation.